Leaf transpiration plays a role in phosphorus acquisition among a large set of chickpea genotypes. (23rd March 2018) - Pang, Jiayin; Zhao, Hongxia; Bansal, Ruchi; Bohuon, Emilien; Lambers, Hans; Ryan, Megan H.; Siddique, Kadambot H.M.
Abstract: Low availability of inorganic phosphorus (P) is considered a major constraint for crop productivity worldwide. A unique set of 266 chickpea ( Cicer arietinum L.) genotypes, originating from 29 countries and with diverse genetic background, were used to study P‐use efficiency. Plants were grown in pots containing sterilized river sand supplied with P at a rate of 10 μg P g −1 soil as FePO4, a poorly soluble form of P. The results showed large genotypic variation in plant growth, shoot P content, physiological P‐use efficiency, and P‐utilization efficiency in response to low P supply. Further investigation of a subset of 100 chickpea genotypes with contrasting growth performance showed significant differences in photosynthetic rate and photosynthetic P‐use efficiency. A positive correlation was found between leaf P concentration and transpiration rate of the young fully expanded leaves. For the first time, our study has suggested a role of leaf transpiration in P acquisition, consistent with transpiration‐driven mass flow in chickpea grown in low‐P sandy soils. The identification of 6 genotypes with high plant growth, P‐acquisition, and P‐utilization efficiency suggests that the chickpea reference set can be used in breeding programmes to improve both P‐acquisition and P‐utilization efficiency under low‐P conditions. Abstract : Low availability of phosphorus (P) is a major constraint for crop productivity worldwide, and there is a need to improve P‐use efficiency. Using a unique set of 266 chickpea genotypes, our study identified 6 genotypes with high P‐acquisition and P‐utilization efficiency, suggesting that the chickpea reference set can be used in breeding programs to improve P‐use efficiency under low‐P conditions. For the first time, our study has demonstrated the significance of leaf transpiration in P acquisition likely via mass flow in chickpea grown in low‐P sandy soils.